Genetic diversity of Pleurotus ostreatus (Jacq.) P. Kumm. strains in Java based on random amplified polymorphic DNA markers - NURAENI EKOWATI; ARIS MUMPUNI; JUNI SAFITRI MULJOWATI; NUNIEK INA RATNANINGTYAS; ARDHINI RIN MAHARNING (Society for Indonesian Biodiversity, 2021)
Abstract. Ekowati N, Mumpuni A, Muljowati JS, Ratnaningtyas NI, Maharning AR. 2021. Genetic diversity of Pleurotus ostreatus (Jacq.) P. Kumm. strains in Java based on Random Amplified Polymorphic DNA markers. Biodiversitas 22: 3488-3493. Genetic variation in a fungal population can occur due to mutation and recombination, resulting in changes in the nucleotides that encode specific DNA sequences. Strains with a high genetic distance and good production capabilities can be used to develop genetic breeding. This study aimed to investigate genetic relationship among Pleurotus ostreatus strains cultivated in Java (Bogor, Cianjur, Tasikmalaya, Purwokerto, Yogyakarta, Tawangmangu, Malang, and Madiun) based on random amplified polymorphic DNA (RAPD) markers. The research method consisted of DNA isolation and DNA amplification using six primers, i.e. OPA2, OPA3, OPA4, OPA7, OPA9, and OPA10. DNA band data were analyzed using NTSYSpc21 software to determine the level of genetic similarity, based on the Unweighted Pair Group Method with Arithmetic Average Algorithm (UPGMA). In all, 101 amplified DNA bands were obtained, with sizes ranging from 136 to 2320 bp and 96.0% of the bands were polymorphic. Based on cluster analysis, it shows that three clusters were formed. There were genetic variations and relationships among eight P. ostreatus strains in Java with a genetic similarity varying from 37-98%.